Pendidikan Karakter Islam dalam Dunia Pendidikan Indonesia - Khalilah Nasution (Jurnal Budi Pekerti Agama Islam, 2024)
Character education consists of two words, namely education and character. The meaning of character education from an Islamic perspective is a conscious effort made by educators towards students which aims to shape the students' personalities and form morals, ethics and a sense of good culture and noble character. Character education is very important at this time because a character will show who we really are, character will determine how a person makes decisions, character determines a person's attitude, words and actions, someone who has good character, then his words and actions will also definitely be good, and all of this will become an identity that unites and personalizes itself, so that it is easy to distinguish it from other identities. The aim of character education in Islamic religious education is to form a person with noble character, because noble character is the basis of all goodness.